Neglected Forearm Fractures and Its Outcome Following Mediolateral Plate Osteosynthesis: A Retrospective Case Series - Sitsabesan Chokkalingam; Ashok T Ramanathan; Gopinath Menon (Journal of Orthopedics and Joint Surgery)
Background: Displaced both bone forearm injuries are essential fractures for fixation. It is not uncommon in certain parts of developing countries for indigenous bone setters to extend their misguided treatment that results in nonunion or malunion of these fractures. The masterly neglect by the patients and the lawful mismanagement by the bone setters cause additional stiffness of the adjacent joints and affect the forearm rotational functions even in the absence of neurovascular compromise. Aim: To assess the clinical and radiological outcome of neglected bone forearm fractures treated with delayed surgical fixation by medial ulnar and lateral radius (MEULAR) plate fixation technique. Materials and methods: The retrospective series includes 11 cases of neglected forearm diaphyseal fractures from January 2019 to November 2022. The mean age in this study group is 32.4 years, with an average time delay of 3.8 months in presentation for the definitive procedure. In these cases, fixation was done using a dynamic compression or locking plate on the medial side of the ulna and lateral side of the radius after open fibroosteoclysis. Both functional and radiological outcomes were assessed with minimum follow-up till the fracture union. Anderson's criteria was used for functional assessment and radiological assessment of radius using bow magnitude, bow percentage and bow ratio. Results: Fracture healing was achieved in all our cases. Functional results were excellent in nine cases and satisfactory in two cases with extended rehabilitation. Restoration of radial bow and interosseous space was feasible with delayed plate osteosynthesis. Conclusion: Delayed fixation in neglected forearm fractures with the MEULAR concept achieves fracture healing with good to excellent functional outcomes. Despite the operative complexity of open osteoclasis or the need for bone grafting, the anatomical radial bow can be restored in the absence of forearm cross-union.